Chinese isms dimensions in mainland China and Taiwan: Convergence and extension of American isms dimensions. Issue 3 (6th September 2017) - Chen, Zhuo Job; Hsu, Kung‐Yu; Zhou, Xinyue; Saucier, Gerard
Abstract: Objective: Previous studies of American English isms terms have uncovered as many as five broad factors: tradition‐oriented religiousness (TR), subjective spirituality (SS), communal rationalism (CR), unmitigated self‐interest (USI), and inequality aversion (IA). The present studies took a similar lexical approach to investigate the Chinese‐language isms structures in both mainland China and Taiwan. Method and Results: In Study 1, exploratory factor analyses with 915 mainland Chinese subjects uncovered four interpretable factors dimensionalizing 165 mainland Chinese dictionary isms terms. These factors represented contents of a combination of TR and SS, USI, CR, and a culturally unique Communist Party of China (CPC) ideology factor. In Study 2, exploratory factor analyses with 467 Taiwan Chinese subjects revealed four interpretable factors categorizing 291 Taiwan Chinese dictionary isms terms. These factors represented contents of a combination of TR and SS, USI, CR, and a culturally unique dimension expressing aspirations for happiness. Conclusions: The results gave evidence for the existence of the isms factors TR and SS, USI, and CR in Chinese culture. Cultural uniqueness was reflected in the merging of TR and SS into the factor Syncretic Religiousness and the culture‐specific factors of CPC ideology in China and Happiness/Peace Promotion in Taiwan.